Catheter‐related thrombosis incidence and risk factors in adult cancer patients with central venous access devices. Issue 12 (22nd December 2020) - Ellis, Marc L.; Okano, Satomi; McCann, Andrew; McDowall, Angela; Van Kuilenburg, Rosita; McCarthy, Alexandra L.; Joubert, Warren; Harper, John; Jones, Mark; Mollee, Peter
Abstract: Background: Central venous access devices (CVAD) are commonly employed in the management of cancer patients. While having several benefits they are associated with significant risks. Aim: To review the incidence and risk factors for catheter‐related thrombosis (CRT) in cancer patients with a CVAD. Methods: We performed a prospective observational cohort study of adult patients with cancer requiring a CVAD between 1 January 2004 and 29 June 2016. The rate of, and risk factors for the development of, symptomatic CRT were evaluated. Results: A total of 4920 central lines was inserted into 3130 patients. The incidence of CRT was 3.6%. CRT developed a median of 12 days following line insertion. Peripherally inserted central catheters (PICC) were associated with the highest rates of CRT (hazards ratio (HR) 22.2, 95% confidence interval (CI) 2.9–170.6). Older age groups developed CRT at lower rates (HR 0.57; 95% CI 0.39–0.84 for age 50–61 years, and HR 0.63; 95% CI 0.45–0.89 for age >61 years) compared to age <50 years. Increased CRT was seen in patients with prior CRT (HR 1.81; 95% CI 1.19–2.77). There was a trend to more CRT events with a Khorana tumour score of 1 compared to those with a score of 0 (HR 1.37, 95% CI 1.00–1.88). Hodgkin lymphoma, germ cell and oesophagus cancers had the highest CRT rates. Side of insertion was not associated with thrombosis risk (HR 0.77; 95% CI 0.57–1.05; P = 0.10). Conclusions: Age <50 years, PICC lines and prior CRT were associated with highest CRT rate. Cancer subtype and insertion side were not predictive of thrombosis.